PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA PT. PEGADAIAN CABANG GUNUNGSITOLI - Gulo, Ardelia; Manalu, Darma; Lumbantobing, Artha; Rajagukguk, Jonson (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of this research is to determine the influence of organizational culture and leadership on employee performance at PT. Gunungsitoli Branch Pawnshop. The method used is an associative quantitative method and data collection techniques using a questionnaire with a sample of 30 respondents. The data analysis methods used are instrument testing, classical assumption testing and hypothesis testing with the help of SPSS 23. The research results show that organizational culture has a positive and significant effect on employee performance, this is indicated by the t-calculated value of the organizational culture variable (X1) which is greater than the t-table value (2.196 > 2.052) with a significance level of 0.00 < 0, 05. Leadership has a positive and significant effect on employee performance, this is shown by the t-calculated value of the leadership variable (X2) being greater than the t-table value (6.741 > 2.052) with a significance level of 0.00 < 0.05. Simultaneously, it was found that organizational culture and leadership had a positive and significant effect on employee performance, this was indicated by the F-count value being greater than the F-table value (31.889 > 3.35) with a significance level of 0.00 < 0.05. The coefficient of determination (r2) value obtained was 0.681, which means that organizational culture and leadership variables can explain employee performance variables by 68.1%, while the remaining 31.9% is influenced by other variables outside of this research variable. It is recommended to PT. Pegadaian Gunungsitoli Branch can encourage its employees to innovate and take the lead in taking risks at work.